Explicit IMF By‐Dependence in Geomagnetic Activity: Quantifying Ionospheric Electrodynamics. Issue 4 (28th April 2021) - Holappa, L.; Robinson, R. M.; Pulkkinen, A.; Asikainen, T.; Mursula, K.
Abstract: Geomagnetic activity is mainly driven by the southward ( B z ) component of the interplanetary magnetic field (IMF), which dominates all solar wind coupling functions. Coupling functions also depend on the absolute value of the dawn‐dusk ( B y ) component of the IMF, but not on its sign. However, recent studies have shown that for a fixed level of solar wind driving, auroral electrojets in the Northern Hemisphere (NH) are stronger for B y  > 0 than for B y  < 0 during NH winter. In NH summer, the dependence on the B y sign is reversed. While this B y sign dependence, also called the explicit B y ‐dependence, is very strong in the winter hemisphere, it is weak in the summer hemisphere. Moreover, the explicit B y ‐dependence is much stronger in the westward electrojet than in the eastward electrojet. In this study, we study how the explicit IMF B y ‐dependence is coupled with large‐scale field‐aligned currents (FACs) by using FAC measurements from the Active Magnetosphere and Planetary Electrodynamics Response Experiment and an empirical ionospheric conductance model. We model the complete ionospheric electrodynamics by solving the current continuity equation, and show that during periods of elevated solar wind driving ( B z  < 0), the IMF B y component modulates Regions 1 and 2 FACs in the dawn sector of the winter hemisphere. This leads to an explicit B y ‐dependence in ionospheric conductance and the westward electrojet. We also show that the B y ‐dependence of FACs and conductance is weak in the dusk sector, which explains the earlier observation of the weak B y ‐dependence of the eastward electrojet. Key Points: For fixed solar wind driving, the westward electrojet in the Northern Hemisphere (NH) is stronger for B y > 0 than for B y < 0 in NH winter The IMF B y component modulates Regions 1 and 2 field‐aligned currents (FACs) in the dawn sector of the winter hemisphere The modulation of FACs by the B y component leads to a modulation of ionospheric conductance and the westward electrojet